Bayesian inverse problems : fundamentals and engineering applications - Chiachío-Ruano, Juan, 1983- (CRC Press, 2021)
"This book is intended to provide a bottom-up and fundamental understanding of the use of probabilistic methods and reliability analysis techniques in engineering applications. It covers from the fundamentals of the theory to real life applications in the field"--